PENGUKURAN KINERJA SOSIAL BANK UMUM SYARIAH (BUS) BERDASARKAN ISLAMIC SOCIAL REPORTING INDEX (INDEKS ISR) (STUDI PADA BANK UMUM SYARIAH (BUS) YANG TERDAFTAR DI STATISTIK PERBANKAN SYARIAH TAHUN 2016-2018) - Rakhmi Ridhawati; Arif Septia Rahman (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
The purpose of this research to measure of Islamic Banking social (BUS) performance based on Islamic Social Reporting Index ( Index of ISR) Study at Islamic Banking (BUS) wich enlist in statistic Islamic 2016-2018. The sampel in this research are 12 Islamic Bank (BUS. Based on results of this research shows the average Islamic Bank socal performance in the 2016-2018 are four Islamc Bank have good predicate, six Islamic Bank have deficient predicate and two Islamic Bank have not good predicate.